THE ROLE OF ABU RAYKHAN BIRUNI’S ATHAR UL-BAQIYA’ IN THE ISLAMIC CIVILISATION - Ganiyev Avazbek Oybekovich (Western European Studies, 2025)
Abu Raykhan Beruni is important in the advancement of Science with his famous works. In this article highlights of the role of Abu Raykhan Biruni’s Athar ul-Baqiya’ in the islamic civilisation
Keywords: Al-Biruni; Athar ul-Baqiya; polymath